Company's Financial Performance Before and During the Covid-19 Pandemic on the Indonesia Stock Exchange - Setiawan, Budi; Basyith, Abdul; Hidayat, Randy (International Journal of Finance Research, 2022)
This study at determine financial performance before and during the Covid-19 pandemic on the Indonesia Stock Exchange. In this study, 29 samples of companies in the health sub-sector, telecommunication services sub-sector, hotel and restaurant tourism sub-sector. This analysis includes company financial analysis, manova test, and research results show that financial performance before and during the Covid-19 pandemic as measured by using CR, DER, TATO, ROE shows no difference in the health sector and for companies in the telecommunication service subsector while in the telecommunication service subsector. Hotel and restaurant tourism shows differences in financial performance before and during the Cobid-19 pandemic. Financial performance such as the Current ratio, DER, TATO and ROE show that younger companies have different financial performances from older companies. the size of the company does not show any difference for the ratio of CR and ROE and shows a difference in the ratio of DER and TATO when it is below 5 trillion